2021
DOI: 10.9734/jpri/2021/v33i28a31527
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Molecular Docking of Moringa Oleifera Leaf Phytochemical Constituents on Alpha Glucosidase, Alpha Amylase and Dipeptidyl Peptidase

Abstract: Moringa oleifera leaf have been used for treatment of diabetes, in this work we studied pancreatic gene expression, trace elements, enzymatic antioxidants, kidney injury biomarkers in streptozocin induced diabetic rats treated with M. oleifera  leaf powder and molecular ducking of M. oleifera  leaf ethanolic, ethyl acetate, hexane and aqueous extracts phytochemicals into protein bank, focusing on the ligands that possesses inhibitory affinity closer to the co-crystalline ligands of alpha amylase, alpha glucosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…According to the data, the leaf extract of Moringa oleifera was considered one of the potential candidates with significant antihyperglycemic activity, particularly in the ethanol and ethyl acetate extracts (93). Recent findings suggested that the extracts successfully reduced the blood glucose levels, increased the insulin levels, decreased the inflammatory cytokines and HOMA-R values, and improved the PPAR gamma levels.…”
Section: Moringa Oleifera: In Vitro Dpp-iv Inhibitory Activitymentioning
confidence: 99%
“…According to the data, the leaf extract of Moringa oleifera was considered one of the potential candidates with significant antihyperglycemic activity, particularly in the ethanol and ethyl acetate extracts (93). Recent findings suggested that the extracts successfully reduced the blood glucose levels, increased the insulin levels, decreased the inflammatory cytokines and HOMA-R values, and improved the PPAR gamma levels.…”
Section: Moringa Oleifera: In Vitro Dpp-iv Inhibitory Activitymentioning
confidence: 99%
“…These bioactive compounds specifically bind to the active site of the enzyme and it may inhibit the enzyme action so it's directly inhibited the disease-causing mosquito development. This kind of study, phytochemical against enzyme inhibition done by various groups, Nwakulite groups describe the co ligands inhibits the amylase activity and control the glucose metabolism (26) . Fatema R. Saber group studied the phytochemical interaction with active site amino acid residue of BChE and ACE enzymes by a mixture H-bonding, and hydrophobic forces (27) .…”
Section: Molecular Docking Studiesmentioning
confidence: 99%